Switching logic-based saturated tracking control for active suspension systems based on disturbance observer and bioinspired X-dynamics. (16th June 2021) - Zhang, Menghua; Jing, Xingjian
Highlights: Potential benefits of system nonlinearities and disturbances are explored. Superior suspension performance with much less energy consumption is guaranteed. Actuator saturation and uncertain dynamics are fully considered at the same time. Abstract: In this paper, by deliberately introducing beneficial nonlinear stiffness and damping characteristics and employing beneficial disturbance effects, a unique switching logic-based saturated tracking control (SLSTC) scheme is proposed for active suspension control. Different from exiting robust control methods, the designed controller switches its structure to cancel out or retain the disturbance based on a novel well-designed disturbance effect indicator; and also, the inherent nonlinearity would be employed instead of directly cancelled by following the introduced bioinspired X-dynamics. The proposed SLSTC method could be for the first time to establish a deliberate assessor on the disturbance effect, and then to make full use of its positive response. These special designs are shown to be very beneficial for improving transient control response and saving control energy significantly. Experimental results validate that, the designed tracking controller can have obvious transient performance improvement up to 63% or more and save the control energy up to 51% or more, compared to traditional controllers. The results of this study would present a novel "robust and green" insight into active suspension control of vehicles by exploiting nonlinear benefits and disturbances.